1989
DOI: 10.3168/jds.s0022-0302(89)79373-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Measurements and Weight on Calf Size and Calving Difficulty of Holsteins

Abstract: Body measurements (heart and paunch girths, wither height, chest depth, pelvic length and width, and body length), body weight, and calving evaluation data (calf birth weight, calf sex, calf presentation, and calving assistance needed) were collected from 1974 parities of 762 Holstein cows between 1968 and 1986. Degree of calving assistance was scored continuously from 1 (no assistance) to 10 (hard mechanical assistance). Phenotypic correlations of dam body traits with calf birth weight were all significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Although we used data from cattle only, our findings support the relationship between lunar phases and parity hypothesized by Ghiandoni et al . In addition, dystocia is a widely accepted risk during first parturition in cows, reflecting smaller sizes and weights of younger primiparous dams [18]. Dystocia can last for several days in heifers, and thus advances or delays in time of birth could be sufficient to influence our findings.…”
Section: Discussionmentioning
confidence: 93%
“…Although we used data from cattle only, our findings support the relationship between lunar phases and parity hypothesized by Ghiandoni et al . In addition, dystocia is a widely accepted risk during first parturition in cows, reflecting smaller sizes and weights of younger primiparous dams [18]. Dystocia can last for several days in heifers, and thus advances or delays in time of birth could be sufficient to influence our findings.…”
Section: Discussionmentioning
confidence: 93%
“…There is evidence in the literature to confirm the above results but it has been shown that nutrition and the energy status of the diet, which affects growth rates, could be related to pelvic measurements. Sieber et al (1989) reported that external pelvic length does not show any significant regression coefficient on milk production, but that higher pelvic width measurements tend to be correlated with larger milk yields. Wiltbank and Remmenga (1982) claimed that heifers on a high-energy diet had a larger precalving pelvic area than did those on a lower nutritional level.…”
Section: Discussionmentioning
confidence: 97%
“…Pelvic-area measurements have been shown to be influenced by age (Price and Wiltbank 1978), breed (Singleton and Nelson 1971), nutrition (Makarechian et al 1987), growth promoters (Anthony et al 198l), and body weight (Sieber et al 1989). Many studies have been conducted in an attempt to predict calving difficulties and birth weight by using skeletal measurements such as the size of the pelvis (Laster 1974;Naazie et al 1989;Schwabe and Hall 1989;van Donkersgoed et al 1990;KO and Ruble 1990;Deutscher 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Schwabe and Hall (1989) investigated the risk factors for dystocia occurring in British breeds of cattle; ease of calving in Friesian heifers was not related solely to fetal birth weights within a range of 37-41 kg. Seiber et al (1989) recorded data from 739 calving dairy heifers; mean fetal birth weight was 38 kg and calving difficulties were associated with delivery of larger calves. Stillbirths associated with heifer calvings have been described frequently in the literature (Dufty 1979: Gee et al 1989: Sluijter et al 1990, the rates varying between 15% and 36%.…”
Section: Discussionmentioning
confidence: 99%